P11.49 An electrophysiological signature of glioma infiltration in the ex vivo human brain. (6th September 2019) - Kirby, A J; Lavrador, J P; Brogna, C; Vergani, F; Chandler, C; Zebian, B; Bodi, I; Bhangoo, R; Ashkan, K; Finnerty, G T
Abstract: BACKGROUND: Invading glioma cells affect the physiological function of the peritumoural cortex. This may manifest clinically as seizures. Here, we investigate the effect the invading glioma cells on the electrophysiological signalling of the peritumoral cortex using living human brain tissue donated by people having a craniotomy for glioma resection (REC approval, 18/SW/002). MATERIAL AND METHODS: The brain tissue was cut into thin slices, which preserved the architecture of the glioma and the adjacent healthy brain. The brain slices were incubated in 5-aminolevulinic acid to make the glioma cells fluorescent. We observed 5-ALA induced fluorescence in both low-grade and high-grade gliomas. This enabled us to make electrophysiological recordings of brain activity across the boundary between glioma and brain. RESULTS: We recorded from brain slices of 5 participants with glioblastoma and 4 participants with oligodendroglioma (WHO grade II - III). Spontaneous "seizure-like" discharges were recorded in brain slices from 5/8 participants (3 GBM, 2 oligodendroglioma) who reported seizures and from one participant (GBM) who had not had any clinical seizures. Further analysis of the electrical discharges revealed that they could be subdivided into two distinct types based on the major frequencies in the discharge. CONCLUSION: We concluded that human brain slices from people with either a low-grade or a high-grade glioma can generate spontaneous seizure-like discharges. This electrophysiological signature will be compared to infiltration and grade of the glioma cells in the donated sample. The living human brain tissue preparation gives us a platform to study the mechanisms of tumour-associated seizures and how abnormal neural activity affects glioma growth.